Nilai Perusahaan pada PT Indofood Tbk Periode 2020–2024: Peran Ukuran Perusahaan dan Struktur Modal (Jurnal Ekonomi Bisnis dan Akuntansi, 2024)
This research attempts to measure the correlation between the scale of the business entity and the external-internal funding configuration (capital structure) on the market appreciation (firm value) of PT Indofood Sukses Makmur Tbk within a five-year fiscal period, namely 2020 to 2024. The method used is a quantity-based approach by processing a total of 20 data points sourced from quarterly financial reports. The entity scale and funding configuration variables function as predictors (independent variables), while corporate value measured using the Price to Book Value (PBV) ratio acts as a predicted (dependent) variable. Multiple regression analysis is applied to verify the hypotheses individually and collectively. The results of the study indicate that individually, the entity scale has significant predictive power, but its relationship is inverse (negative) to firm value, implying that the expansion of total assets is not always accompanied by an increase in market optimism towards the company's valuation. Conversely, the funding configuration does not show a significant influence on firm value, which concludes that modification of the portion of liabilities (debt) in assets does not play a vital role in determining the company's PBV. However, when tested simultaneously, it is evident that entity scale and financing configuration significantly contribute to determining firm value. This finding underscores the importance of efficiency in asset expansion and prudence in designing financing policies as crucial strategies for sustainably maintaining market valuations.